Nutritional knowledge, sleep duration, and screen time are related to consumption of sugar-sweetened beverage on students of Junior High School 11 Jakarta - Eva Nurjayanti; Nur Setiawati Rahayu; Anna Fitriani (UHAMKA PRESS, 2020)
Consumption of sugar-sweetened beverages in adolescents is still high, because of the sinful lifestyle, like not getting enough sleep and high screen time. The study aims to determine the relationship of nutritional knowledge, the role of parents, duration of sleep, and screen time with the level of consumption of sweetened-beverage. This study used a cross-sectional design with systematic random sampling. The number of subjects was on 165 students of class VII and VIII of Junior High School 11 Jakarta. Data nutritional knowledge, parental roles, sleep duration, and screen time were obtained from interviews using a questionnaire. The level of consumption of sweetened drinks was obtained from interviews using Semi-Quantitative Food Frequency Questionnaires (SQ-FFQ). Most subjects had a high level of consumption of sweet-beverages (60.6%), good nutritional knowledge (64.8%), the role of parents is classified at risk (50.9%), less duration of sleep (77%) and high screen time (72.1%). There was a relationship between nutritional knowledge, sleep duration, and screen time with the level of consumption of sugar-sweetened beverages. Keywords: Nutritional Knowledge, Screen Time, Sleep Duration, Sugar-Sweetened Beverage